Pengaruh Keterikatan Kerja dan Dukungan Sosial terhadap Kepuasan Kerja pada Guru - Farouq Fathurrahman; Desi Nur’aini; Jean Rala Bangkit; Nada Fristy Yusri (Journal on Education, 2025)
In educational institutions, teachers are a very important asset because with teachers the school will be able to achieve educational goals. Therefore, foundations and schools need to pay attention to one of the fulfillment of teacher needs, namely job satisfaction so that teachers can enjoy their work activities better. This study aims to test the effect of work engagement and social support on job satisfaction in teachers. This study involved 103 high school and junior high school teachers in the provinces of DKI Jakarta, West Java and Banten with multiple linear regression test analysis techniques. The results of this study indicate that the proposed hypothesis is accepted, namely that there is an effect of work engagement and social support on job satisfaction in teachers.